2007
DOI: 10.4314/ijmu.v1i2.39835
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Depression and Assertiveness in Normal Population and Depressed Individuals

Abstract: The present study is aimed at exploring the relationship between depression and self-assertiveness. Sample of the study consisted of 100 people (men = 50, women = 50), who were taken from different offices, houses, and hospitals. Their age ranged between 18 to 50 years, and education level was at least middle standard and above. Their marital status was of both types i.e. married and unmarried. They belonged to lower and middle socioeconomic status. For the measurement of depression and self-assertiveness Urdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The results obtained in the present study on the positive relationship between the assertiveness of women with social self-control and the absence of such a connection in men cannot be compared with other studies of this issue in view of the fact that they were not found. The opinion of foreign researchers 28,8,13,15 about the positive relationship between levels of assertiveness and job satisfaction was found in us only for women, but not for men. The revealed absence in our men of the relationship of assertiveness with satisfaction with life also diverges from the conclusion of foreign psychologists 9,15 who assert that assertiveness positively and statistically highly correlates with the satisfaction of the life of both men and women.…”
Section: Notation Inmentioning
confidence: 83%
“…The results obtained in the present study on the positive relationship between the assertiveness of women with social self-control and the absence of such a connection in men cannot be compared with other studies of this issue in view of the fact that they were not found. The opinion of foreign researchers 28,8,13,15 about the positive relationship between levels of assertiveness and job satisfaction was found in us only for women, but not for men. The revealed absence in our men of the relationship of assertiveness with satisfaction with life also diverges from the conclusion of foreign psychologists 9,15 who assert that assertiveness positively and statistically highly correlates with the satisfaction of the life of both men and women.…”
Section: Notation Inmentioning
confidence: 83%
“…For example, individuals with social anxiety often adopt passive and avoidant behaviors [ 11 , 12 ], repressing high levels of anger and hostility [ 13 ]. Moreover, unassertiveness correlates with depressive symptoms [ 5 , 14 ], contributing to both the onset and the deterioration of depressive symptoms [ 15 , 16 ]. Lastly, assertiveness negatively correlates with psychological distress [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that India has a patriarchal culture that encourages power-distance and uncertainty-avoidance in relationships [5,6]. They are prone to be non-assertive, passive as well as meek in interpersonal situations [7] due to which many of them, especially adolescents, face confusion and stress.…”
Section: Introductionmentioning
confidence: 99%